Employability skills of state vocational high school students on welding engineering expertise competency - Hafiidhiya Janata Areisy; Putu Sudira (Jurnal Pendidikan Vokasi, 2022)
This study aims to: 1.) Describe the mastery level of employability; and 2.) Find out the order of mastery of the employability skills of vocational high school (VHS) students. This study was a survey research with quantitative approach. The research was conducted at a vocational high school in Madiun Regency with A accreditation. Data collection instrument was a questionnaire that had been tested for content validity by the experts. The construct validity test used the product-moment formula and was declared valid. The results that 56 items were declared valid and reliable. The questionnaire was given to 149 students of class XII of welding engineering expertise competency. Data were analyzed using descriptive statistical analysis technique. The results of the study are as follows: 1.) The mastery level of employability skills is in the high category with the mean score 168.61 greater than the ideal mean score of 132.5; and 2.) The order of mastery on aspects of employability skills, from the highest to the lowest achievement using technology skill, keeping occupational health and safety skill, learning skill, self-management skill, initiative and enterprise skill, planning and organizing skill, communication skill, and problem-solving skill.